Brassica carinata biomass, yield, and seed chemical composition response to nitrogen rates and timing on southern Coastal Plain soils in the United States. Issue 8 (4th June 2021) - Bashyal, Mahesh; Mulvaney, Michael J.; Lee, Dewey; Wilson, Chris; Iboyi, Joseph E.; Leon, Ramon G.; Landry, Gabriel M.; Boote, Kenneth J.
Abstract: Brassica carinata (carinata), a non‐food oilseed feedstock mainly used for biofuel, is a relatively new alternative winter crop in the southeastern (SE) United States (US). However, there are limited N rate and N application timing data available at the regional scale. These data are needed to expand production in the SE US. An N rate study was conducted during the winter–spring growing seasons during 2017–2018 and 2018–2019 in Florida, US, and at three locations during 2018–2019 in Georgia, US, to quantify the effects of N rate (0, 45, 90, 134, and 179 kg N ha −1 ) on carinata nutrient uptake, biomass, seed yield, and seed chemical composition. Seed yield showed a linear response up to 134 kg N ha −1 . Seed protein and glucosinolate concentrations decreased from 0 to 90 kg N ha −1, then increased from 90 to 179 kg N ha −1 . Seed oil concentration was inversely related to seed protein concentration. A two‐factor N application timing study (4 N application timing: at‐plant, pre‐bolting, at‐plant + pre‐bolting, at‐plant + pre‐bolting + bolting × 4 N rates: 0, 45, 90, and 134 kg N ha −1 ) was conducted in Georgia, US, over three site‐years to quantify the effect of N application timing on yield and agronomic and economic optimum N rates (AONR and EONR, respectively). All split applications increased AONR by at least 10 kg N ha −1 compared to a single at‐plant application. A two‐split N application was more profitable than either a single N application or a three‐split N application based on marginal return. A two‐way split application (at‐plant + pre‐bolting) at 134 kg N ha −1 is recommended to optimize yield and economical production. Based on uncertainty analyses, the 50% credible interval of EONR occurred between 116 and 152 kg N ha −1, with a median estimate at 130 kg N ha −1 . Abstract : There are limited N rate and N application timing data available at the regional scale to expand carinata production in the southeastern (SE) United States (US). This research quantified the effects of applied N rates on carinata nutrient uptake, biomass, seed yield, and seed chemical composition over five site‐years on Coastal Plain soils in the SE US. The effect of N application timing on seed yield, agronomic and economic optimum N rates over three site‐years was also quantified. Based on the results, 134 kg N ha −1 as a two‐way split application (at‐plant + pre‐bolting) is recommended for profitable production.